THE ROLE OF ENGLISH VAGANZA COMPETITION 2016 ON CHALLENGING IMPROMTU SPEECH - Pipit Rahayu (English Study Program University of Pasir Pengaraian, 2017)
The purpose of this study was to investigate how students’ language in the English Vaganza competition which was organized by the University of PasirPengaraian. The type of research was descriptive quantitative. Researchers used video footage of students’ performance. The research instrument used video recording. Sampling was total sampling. The sample consists of 19 students who follow the impromptu speech competition in EnglishVaganza. The data obtained comes from several raters. The data were taken from the video recording of the students' performances and transcripts from each student itself. The ways to analyze data were collecting data, analyzing data, and display the results of the data analysis itself. In taking the data, the researcher used video recording and raters. In analyzing the data, the researcher used indicators in impromptu speech; say the objectives, composing contents, supporting ideas, adding stories and examples and summarizing key ideas, showing awareness of the listener's needs, speaking clearly, choosing the right vocabulary and information, using tone, speed and word size thinking, complexity of the vocabulary and last showing comfort with the listener. Based on the result of the research, it was concluded that the level of speech impromptu of students in the English Vaganza competition was quite good.